Indonesia In Cop 26: Over Ambition On National Determined Contribution - Muhammad Fauzan Alamari (Mandala: Jurnal Ilmu Hubungan Internasional, 2022)
Climate change has been the world hottest issue since the fall of cold war. Where the world states once again gather to find solution regarding this circumstance. From first COP until the latest 26thCOP. The world yet to find best solution to cope with this issue, either it was the ideas or the commitment to solve it. Indonesia is one of the parties that involve in COP but yet to give the best possible efforts join the world force to commit to the same agreement that was signed together. Indonesia gave the same ambition on paper but not in the implementations. The presence of fossils energy such as coal as the biggest share in Indonesia export and domestic consumption made it dilemmatic for Indonesia to commit in COP.